Fungsi Keluarga Sebagai Pembentukan Karakter Islami Anak di Tk Allam Desa Pelemwatu Kecamatan Menganti Kabupaten Gresik - Wulan, Fitrianti Wulandari; Novita Widyaningrum; Umi Matsturoh (Institut Agama Islam Negeri Madura, 2024)
The family as an informal educational institution plays an important role in forming the Islamic character of early childhood. The function of the family as a place to cultivate children's character is the responsibility of parents. It is the responsibility of parents to provide religious education, moral values, culture, personality and self- skills as members of society. The aim of this article is to describe (1) implementation of family functions; and (2) the formation of Islamic character of early childhood. This article uses a qualitative research method with a case study approach The location of this research is the Allam Kindergarten in Pelemwatu Village, Menganti District, Gresik Regency. The research subjects were five families. The subjects of the research were five families. Data collection using observation techniques, interviews, and document study. The results of the study provide an overview of the implementation of family functions reflected in three functions namely: the religious function, the educational function, and the socialization function. In forming the Islamic character of early childhood in sub-urban families, it is reflected in three Islamic characters, namely: noble character, love of truth, and exemplary. The conclusions from the implementation of family functions in the formation of the Islamic character of early childhood in sub-urban families provide an overview of the function of the family as a center for instilling religious values, as the first place of education, and as a means of socializing children to know rules, traditions, religious values and norms. In addition, the family is the place for the formation of Islamic noble character. love the truth, and exemplary children to become a person who has good manners, smiles generously, monotheism, gentleness, and becomes a positive person in the family, school and community environment.